Electrolytic hydrogen production catalyst, anode and preparation method, activation method and application thereof

By doping barium into the electrolytic hydrogen production catalyst and forming a sulfate activation layer, the problems of insufficient anode corrosion and stability in seawater electrolysis are solved, and efficient and stable hydrogen production by seawater electrolysis is achieved.

CN119144993BActive Publication Date: 2025-04-18NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410452007.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-06-16
Filing Date
2024-04-15
Publication Date
2025-04-18
Estimated Expiration
2044-04-15

AI Technical Summary

Technical Problem

During the direct hydrogen production process of seawater electrolysis, the kinetics of the anode oxygen evolution reaction are slow, and high concentrations of chloride ions lead to anode corrosion, resulting in shortening of service life, and the existing catalysts are insufficient in seawater.

Method used

An electrolytic hydrogen production catalyst is provided, with the chemical formula of [M1-xNxM'(OH)2]x+[(An-)x/n·mH2O]x-, prepared by hydrothermal reaction, containing scandium, vanadium, chromium, manganese, iron, cobalt, and nickel plasma, doped with alkaline earth metal elements, such as barium, forming an atomic dispersion structure, and forming a sulfate activation layer on the surface of the catalyst.

Benefits of technology

This catalyst significantly improves the stability and corrosion resistance of the anode in the production of hydrogen by seawater electrolysis, extends the service life, while maintaining excellent catalytic performance and low cost characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144993B_ABST
    Figure CN119144993B_ABST
Patent Text Reader

Abstract

The present application discloses a hydrogen electrolysis catalyst, an anode, and a preparation method, an activation method, and an application thereof. In one embodiment, the hydrogen electrolysis anode includes a catalyst, and the catalyst is nickel-iron-barium hydrotalcite, which has a nano-hexagonal sheet structure and a thickness of 100 to 200 nm. The catalyst can be prepared by a one-step solvent thermal reaction method. In the present application, by uniformly doping alkaline earth metal ions in nickel-iron hydrotalcite and making them atomically dispersed, the hydrogen electrolysis anode based on the catalyst can be used in the process of hydrogen electrolysis of aqueous solution containing chloride ions. It can not only maintain excellent catalytic performance, but also greatly improve the performance of resistance to chloride ion corrosion, and significantly improve the working stability and service life.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims priority to the Chinese invention patent application with application number CN202310720257.3, application date June 16, 2023, and name “Electrolysis Hydrogen Anode and Preparation Method, Activation Method and Application”, and the above patent application is incorporated herein by reference in its entirety. Technical Field

[0002] The present application belongs to the field of material and energy catalysis technology, and specifically relates to an electrolytic hydrogen production catalyst, an anode, and a preparation method, activation method and application thereof. Background Art

[0003] Carbon emissions from the energy industry account for 2 / 3 of the world's total greenhouse gas emissions. Hydrogen is one of the most promising energy carriers that can replace fossil fuels and address future global warming effects. Hydrogen production from water electrolysis driven by renewable energy can provide a new way to alleviate current energy shortages without affecting environmental sustainability.

[0004] The hydrogen produced by water electrolysis is of high purity, and the high energy consumption of water electrolysis can be reduced through technical means, but the limited freshwater resources will greatly restrict the development and large-scale application of water electrolysis. From a practical point of view, direct seawater electrolysis has huge advantages. The abundant seawater reserves on the earth are the basic support for the large-scale application of seawater electrolysis, and it also has the ability to produce high-purity hydrogen.

[0005] However, there are some more serious problems to be solved when using seawater electrolysis directly. For example, hydrogen production by seawater electrolysis apparently includes two half reactions, namely the anode oxygen evolution reaction and the cathode hydrogen evolution reaction. Under alkaline conditions, the kinetics of the oxygen evolution reaction (OER) are slow, and the high concentration of chloride ions in seawater will compete with the anode oxygen evolution reaction and cause severe corrosion to the anode, resulting in a shortened service life. Although catalysts such as RuO2 and IrO2 have been used as anodes for electrolysis, there is an urgent need to develop OER catalysts with high activity, high selectivity, good stability, low cost, and abundant reserves.

[0006] In previous studies, a series of OER catalysts in alkaline solutions have been developed, including hydroxides, metal oxides, sulfides, and phosphides. However, at industrial current densities, seawater electrolysis has not yet achieved long-term stability (100 to 1000 hours). Therefore, the development of efficient and stable anodes for electrolyzing seawater to produce oxygen has become an urgent need.

[0007] Some non-precious metal oxygen evolution catalysts nickel-iron hydrotalcite (refer to CN114657591A, CN114657591B) have been widely reported and studied due to their excellent performance and low cost. However, they are easily corroded in seawater, resulting in a short service life, which seriously limits their application in aqueous solutions containing chloride ions, especially in seawater electrolysis for hydrogen production. Summary of the invention

[0008] The main purpose of the present application is to provide a catalyst for hydrogen production by electrolysis, an anode and a preparation method, an activation method and an application thereof, so as to overcome the deficiencies existing in the prior art.

[0009] In order to achieve the aforementioned invention objectives, the technical solutions adopted in this application are as follows:

[0010] The first aspect of the present application provides a catalyst for electrolytic hydrogen production, the chemical formula of which is [M 1-x N x M'(OH)2] x+ [A n- ) x / n ·mH2O] x- , M and N are any two ions of scandium, vanadium, chromium, manganese, iron, cobalt and nickel, and M and N are in chemical valence states of +2 and +3, respectively, M' is selected from alkaline earth metal ions and is atomically dispersed in the catalyst, A n- Selected from CO3 2- 、NO3 2- , Cl - OH - or SO4 2- , x=0.17~0.33, m is an integer greater than or equal to 0, and n=1~3.

[0011] The second aspect of the present application provides a method for preparing a hydrogen electrolysis catalyst, which comprises: subjecting a mixed reaction liquid containing M, N and M' to a hydrothermal reaction to prepare a hydrogen electrolysis catalyst, wherein the chemical formula of the catalyst is [M 1-x N x M'(OH)2] x+ [(A n- ) x / n ·mH2O] x- , wherein M and N are any two ions of scandium, vanadium, chromium, manganese, iron, cobalt, and nickel, and M and N are in the chemical valence states of +2 and +3, respectively, M' is selected from alkaline earth metal ions and is atomically dispersed in the catalyst, A n- Selected from CO3 2- 、NO3 2- , Cl - OH - or SO4 2-, x=0.17~0.33, m is an integer greater than or equal to 0, and n=1~3.

[0012] The third aspect of the present application provides an activated electrolytic hydrogen production catalyst, which includes the electrolytic hydrogen production catalyst and a sulfate activation layer, wherein the sulfate activation layer includes sulfate ions distributed on the surface of the catalyst, and the sulfate ions are combined with alkaline earth metal ions in the catalyst.

[0013] The fourth aspect of the present application provides a seawater electrolysis hydrogen production anode, which includes the electrolysis hydrogen production catalyst or the activated electrolysis hydrogen production catalyst.

[0014] The fifth aspect of the present application provides the use of the electrolytic hydrogen production catalyst, the activated electrolytic hydrogen production catalyst or the electrolytic hydrogen production anode in electrolytic hydrogen production.

[0015] The sixth aspect of the present application provides a method for producing hydrogen by electrolysis, which comprises: placing the anode and cathode of the hydrogen production by electrolysis into an aqueous solution containing chloride ions, and applying a working voltage between the anode and the cathode, thereby achieving hydrogen production by electrolysis.

[0016] The seventh aspect of the present application provides an electrolytic hydrogen production system, comprising an anode and a cathode, wherein the electrolytic hydrogen production system is used to produce hydrogen by electrolyzing an aqueous solution containing chloride ions, and the anode comprises the electrolytic hydrogen production anode.

[0017] Compared with the prior art, this application has at least the following beneficial effects:

[0018] (1) The provided electrolytic hydrogen production catalyst provides a rich coordination environment for alkaline earth metal elements such as Ca, Sr, and Ba through the oxygen sites on the surface of hydrotalcite, so that they can be uniformly doped in the hydrotalcite in the form of atomic-level dispersion, wherein the alkaline earth metal element is preferably Ba; and, during the synthesis process, by controlling the addition amount of the alkaline earth metal element to 0.1 to 1 mmol / L, it can be ensured that the excellent catalytic performance is maintained, and the working current is 400 mA / cm 2 In the three-electrode system, the voltage range is 1.52~1.55V.

[0019] (2) The provided electrolytic hydrogen production catalyst can maintain excellent catalytic performance and anode catalytic selectivity of more than 99.7% when applied to the electrolytic hydrogen production process of chloride ion-containing aqueous solution by adding atomically dispersed doping elements and only requires simple activation treatment, and the stability is significantly improved.

[0020] (3) The preparation process of the electrolytic hydrogen production catalyst provided is simple and can be achieved by a one-step solvent thermal reaction. The raw materials are cheap and readily available, making it suitable for large-scale production. This is of great significance for promoting the popularization and application of seawater electrolysis hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 This is the X-ray diffraction pattern of the electrolytic hydrogen production anode provided in Example 2.

[0023] Figure 2 This is an electron microscope photograph of the surface morphology of the electrolytic hydrogen production anode provided in Example 2.

[0024] Figure 3 This is a scanning transmission electron microscope photograph of the electrolytic hydrogen production anode provided in Example 2.

[0025] Figure 4 This is a spherical aberration transmission electron microscope photograph of the electrolytic hydrogen production anode provided in Example 2.

[0026] Figure 5 This is a test diagram of the electrolysis stability of the electrolysis hydrogen production anode provided in Example 2.

[0027] Figure 6 This is the X-ray photoelectron spectrum of the electrolytic hydrogen production anode provided in Example 4.

[0028] Figure 7 This is a test diagram of the electrolysis stability of the electrolysis hydrogen production anode provided in Example 5.

[0029] Figure 8 This is an electron microscope photograph of the surface morphology of the electrolytic hydrogen production anode provided in Example 5.

[0030] Fig. 9 This is a test diagram of the electrolysis stability of the electrolysis hydrogen production anode provided in Example 5.

[0031] Fig.10 This is a test diagram of the electrolysis stability of the electrolysis hydrogen production anode provided in Example 6.

[0032] Fig.11 This is a test diagram of the electrolysis stability of the electrolysis hydrogen production anode provided in Example 7.

[0033] Fig.12 This is a test diagram of the electrolysis stability of the electrolysis hydrogen production anode provided in Example 8.

[0034] Fig.13 This is a test diagram of the electrolysis stability of the electrolysis hydrogen production anode provided in Comparative Example 1.

[0035] Fig.14 This is a test diagram of the electrolysis stability of the electrolysis hydrogen production anode provided in Comparative Example 2.

[0036] Fig.15 This is a test diagram of the electrolysis stability of the electrolysis hydrogen production anode provided in Example 3. DETAILED DESCRIPTION

[0037] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of this application after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows.

[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application may also be implemented in other ways different from those described herein. Therefore, the scope of protection of the present application is not limited to the specific embodiments disclosed below.

[0039] Furthermore, relational terms such as "first" and "second" and the like are merely used to distinguish one substance or method step from another substance or method step having the same name, but do not necessarily require or imply any such actual relationship or order between these substances or method steps.

[0040] Some embodiments of the present application provide a catalyst for hydrogen production by electrolysis, the chemical formula of which is [M 1-x N x M'(OH)2] x+ [(A n- ) x / n ·mH2O] x- , M and N are any two ions of scandium, vanadium, chromium, manganese, iron, cobalt and nickel, and M and N are in chemical valence states of +2 and +3, respectively, M' is selected from alkaline earth metal ions and is atomically dispersed in the catalyst, A n- Selected from CO3 2- 、NO3 2- , Cl - OH - or SO4 2- . Wherein, x = 0.17 to 0.33. m is an integer greater than or equal to 0, preferably a natural number, and generally m decreases as x increases. n = 1 to 3. In some cases, m can be calculated according to the following formula, that is, m = (1-α×x / n), α is A n- The number of positions occupied in the layered structure of the catalyst. In some cases, m can have a value of 1-9.

[0041] In one embodiment, the catalyst has at least one of the following characteristics:

[0042] ix) M and N are any two ions of iron, cobalt and nickel;

[0043] x) M' is selected from Ca 2+ , Sr 2+ Or Ba 2+ ;

[0044] xi)A n- Selected from CO3 2- 、NO3 2- OH - or SO4 2- ;

[0045] xii) The atomic percentage content of M' in the catalyst is 0.4% to 0.5%.

[0046] Furthermore, the catalyst has at least one of the following characteristics:

[0047] 1)M' is Ba 2+ ;

[0048] 2) A n- Selected from CO3 2- or SO4 2- .

[0049] For example, M and N are Ni 2+ , Fe 3+ , M' is Ba 2+ , A n- For CO3 2- .

[0050] In the present application, M' is preferably Ba 2+ For example, the catalyst is nickel-iron hydrotalcite doped with barium, wherein M and N are Ni 2+ , Fe 3+ , and the atomic percentage content of barium in the catalyst is 0.4% to 0.5%. If the barium content is too low, it will lead to less fixed sulfate ions and fail to fully protect the catalyst. Conversely, if the barium content is too high, it will have a negative impact on the catalytic performance.

[0051] In one embodiment, the catalyst has a nano hexagonal platelet structure.

[0052] Furthermore, the nano hexagonal sheet structure has at least one of the following characteristics: a) a thickness of 100 to 200 nm; b) an area of ​​0.01 to 0.05 μm 2 .

[0053] Taking the catalyst as an example of nickel-iron hydrotalcite doped with barium, when the catalyst is used to prepare an anode and used for electrolysis of an aqueous solution containing chloride ions to produce hydrogen, if the aqueous solution contains sulfate ions, the sulfate ions will react with the barium ions in the catalyst to generate barium sulfate, forming a fixed sulfate activation layer (hereinafter referred to as sulfate activation layer or chlorine expulsion layer) to expel chlorine, hindering the continued adsorption of other chloride ions in the solution on the catalyst surface, thereby delaying chloride ion corrosion, improving the stability of the catalyst and the corrosion resistance of the anode, and greatly extending the service life of the anode. At the same time, the barium and barium sulfate nanolayer structures doped in appropriate amounts do not substantially affect the catalytic activity of the catalyst. When the aqueous solution does not contain or contains less sulfate ions, the catalyst can be activated in advance by an alkaline sulfate solution to form the aforementioned sulfate activation layer on its surface, and then applied to electrolysis of an aqueous solution containing chloride ions to produce hydrogen, which also achieves the effect of improving the stability of the catalyst and the corrosion resistance of the anode and extending the service life of the anode.

[0054] Some embodiments of the present application also provide a method for preparing the electrolytic hydrogen production catalyst, which comprises: subjecting a mixed reaction liquid containing M, N and M' to a hydrothermal reaction to obtain an electrolytic hydrogen production catalyst, wherein the chemical formula of the catalyst is [M 1-x N x M'(OH)2] x+ [(A n- ) x / n ·mH2O] x- , wherein M and N are any two ions of scandium, vanadium, chromium, manganese, iron, cobalt, and nickel, and M and N are in the chemical valence states of +2 and +3, respectively, M' is selected from alkaline earth metal ions and is atomically dispersed in the catalyst, A n- Selected from CO3 2- 、NO3 2- , Cl - OH - or SO4 2- , the values ​​of x, m, and n are as shown above.

[0055] In one embodiment, the preparation method specifically includes: subjecting a mixed reaction liquid containing a first transition metal compound, a second transition metal compound and an alkaline earth metal compound in a molar ratio of 2-5:2-5:0.4-1 to a hydrothermal reaction at 90-120°C to obtain the catalyst; wherein the first transition metal compound, the second transition metal compound and the alkaline earth metal compound contain M, N and M', respectively, and the pH value of the mixed reaction liquid is 8-10.

[0056] In one embodiment, the preparation method further specifically comprises:

[0057] The first transition metal compound, the second transition metal compound, the alkaline earth metal compound and water are mixed to form a metal salt solution, and an alkaline substance is added to adjust the pH value of the metal salt solution to 8-10, thereby obtaining the mixed reaction solution;

[0058] The mixed reaction liquid is reacted at 90-120° C. for 8-12 hours to obtain the catalyst.

[0059] In one embodiment, the first transition metal compound includes soluble nickel salts such as nickel nitrate and nickel chloride, the second transition metal compound includes soluble iron salts such as iron nitrate and iron chloride, and the alkaline earth metal compound includes soluble alkaline earth metal salts such as barium nitrate and barium chloride.

[0060] In one embodiment, the concentrations of the first transition metal compound, the second transition metal compound, and the alkaline earth metal compound contained in the mixed reaction solution are 0.1-1 mmol / L, 0.2-0.5 mmol / L, and 0.1-1 mmol / L, respectively.

[0061] In one embodiment, the alkaline substance includes any one or more combinations of urea, hexamethylenetetraammonium or triethanolamine, but is not limited thereto.

[0062] The preparation method of the electrolytic hydrogen production catalyst described in the present application can be achieved through a one-step solvent thermal reaction, which is simple to operate and does not require harsh reaction conditions such as high temperature and high pressure and expensive reaction equipment. In addition, the raw materials are mainly common metal salts, which are cheap and easy to obtain, low cost, and environmentally friendly.

[0063] Some embodiments of the present application also provide an activated electrolytic hydrogen production catalyst, which includes the electrolytic hydrogen production catalyst and a sulfate activation layer, wherein the sulfate activation layer includes sulfate ions distributed on the surface of the catalyst, and the sulfate ions are combined with the alkaline earth metal ions in the catalyst. Further, after the sulfate ions are combined with the alkaline earth metal ions, a nanolayer structure can be formed on the surface of the catalyst, and the nanolayer structure is mainly composed of nanoparticles with a particle size greater than 0 but less than 5nm. For example, if the alkaline earth metal ions are barium ions, the nanoparticles are barium sulfate nanoparticles.

[0064] Some embodiments of the present application also provide a method for activating a catalyst for hydrogen production by electrolysis, which comprises: placing the catalyst in an alkaline solution containing sulfate ions, and performing an activation treatment by an electrochemical method.

[0065] In one embodiment, the electrochemical method for activation includes but is not limited to cyclic voltammetry.

[0066] For example, the electrochemical method is cyclic voltammetry, in which the scanning voltage used is 0V to 1V, the scanning voltage speed is 5mV / s to 50mV / s, and the number of scanning circles is 10 to 30 circles, so as to evenly distribute the aforementioned nanoparticles and avoid their agglomeration.

[0067] In one embodiment, the alkaline solution contains sulfate ions at a concentration of 0.01 to 0.1 mol / L, so that the aforementioned nanoparticles are small and evenly distributed, and do not affect the catalytic active area after covering the catalyst surface, that is, the formed sulfate active layer can both block the entry of chloride ions and leave enough channels for water molecules to contact the catalyst.

[0068] In one embodiment, the alkaline solution contains sulfate, and the sulfate includes sodium sulfate or potassium sulfate, etc., but is not limited thereto.

[0069] In one embodiment, the alkaline solution contains an alkaline substance with a concentration of 0.1 to 1 mol / L, wherein the alkaline substance may include but is not limited to sodium hydroxide or potassium hydroxide.

[0070] Some embodiments of the present application also provide an electrolytic hydrogen production anode, which includes the electrolytic hydrogen production catalyst or the activated electrolytic hydrogen production catalyst.

[0071] In one embodiment, a plurality of the catalyst nanosheets are vertically disposed on the surface of the anode and are densely arranged to form an array structure.

[0072] In one embodiment, the specific surface area of ​​the array structure is 40 to 50 m 2 / g.

[0073] In one embodiment, the anode further includes a conductive substrate for supporting the catalyst, and the conductive substrate includes foamed nickel, nickel mesh, foamed iron, foamed nickel-iron, etc., but is not limited thereto.

[0074] In some cases, the conductive substrate may also be considered a current collector for the anode.

[0075] Some embodiments of the present application also provide a method for preparing the electrolytic hydrogen production anode, comprising: placing the conductive substrate into the mixed reaction solution comprising a first transition metal compound, a second transition metal compound and an alkaline earth metal compound in a molar ratio of 2-5:2-5:0.4-1, and performing a hydrothermal reaction at 90-120°C, thereby in-situ generating the electrolytic hydrogen production catalyst on the conductive substrate.

[0076] Exemplarily, the method for preparing the electrolytic hydrogen production anode is to prepare the nickel iron barium hydrotalcite electrolytic hydrogen production anode by a one-step hydrothermal method, and the specific steps are as follows:

[0077] (1) A first transition metal compound, a second transition metal compound and an alkaline earth metal compound are mixed in a molar ratio of 2-5:2-5:0.4-1, and then an aqueous solution is added to obtain a metal salt solution, and an alkaline substance is added to adjust the pH to 8-10.

[0078] Preferably, the first transition metal compound comprises a nickel salt, and the second transition metal compound comprises an iron salt.

[0079] (2) Adding a conductive substrate to the mixed solution, reacting at 90-120° C. for 8-12 hours to obtain an anode material.

[0080] As some typical application examples, a solution prepared by using nickel-iron hydrotalcite as a solvent can be used to slowly grow a densely coated catalyst in situ on a conductive substrate to serve as a comparative anode; a solution prepared by using nickel-iron-barium hydrotalcite as a solvent can be used to slowly grow a densely coated catalyst in situ on a conductive substrate, and the prepared anode catalyst has excellent electrocatalytic seawater oxygen evolution performance and resistance to chlorine corrosion, and therefore, the anode can be used for catalytic electrolysis to produce hydrogen.

[0081] In the process of hydrogen production by electrolysis without sulfate, the catalyst loaded on the anode, i.e., nickel-iron-barium hydrotalcite, can be activated in advance in a sulfate solution to fix a sulfate layer on its surface; in the process of hydrogen production by electrolysis containing sulfate, sulfate ions in the solution will react with barium in the hydrotalcite to generate barium sulfate, forming a fixed sulfate layer to discharge chlorine, thereby hindering the continued adsorption of other chloride ions in the solution on the electrode surface, thereby delaying the corrosion of the anode by chloride ions, and the appropriate doping of barium and barium sulfate nanolayer structure will not have a significant impact on the catalytic effect of the anode, thereby improving the stability of the anode in the seawater electrolysis hydrogen production reaction.

[0082] Of course, the above technical solution may also include the steps of testing and characterizing the material and the selectivity and stability of the anode for hydrogen production by seawater electrolysis after the anode is obtained. These steps may be for quality control or for in-depth research. Whether or not the characterization is performed and by what means, they all fall within the scope of protection of this application. The material characterization of the modified anode may include but is not limited to: X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) characterization to determine the material properties after coating; scanning electron microscopy (SEM), transmission electron microscopy (TEM) to characterize the material morphology, lattice and element content; the selectivity and stability of the modified anode may include but is not limited to: linear sweep voltammetry (LSV) and it constant current test.

[0083] The inventors have found that the morphology, thickness, and sheet coverage of the nickel iron barium nanosheets are key features for effectively removing chlorine without having a significant negative impact on catalytic efficiency. To form this feature, it is necessary to uniquely design the process parameters for depositing the nickel iron barium nanolayer to form the special morphology, such as the solution concentration, hydrothermal temperature, and hydrothermal time during hydrothermal deposition. Only by setting a suitable deposition process can the special nickel iron barium nanolayer morphology be formed.

[0084] In one embodiment, the preparation method of the electrolytic hydrogen production anode includes uniformly doping barium in the anode by a hydrothermal method, wherein the hydrothermal solution used includes nickel salt, alkaline earth metal salt and iron salt in a molar ratio of 2-5:0.4-1:2-5, and additional alkaline substances, the alkaline earth metal salt includes but is not limited to barium nitrate, and the concentration of the alkaline earth metal salt in the hydrothermal solution is 0.1-1 mmol / L; the nickel salt includes but is not limited to nickel nitrate, and the concentration of the nickel salt in the hydrothermal solution is 0.1-1 mmol / L; the iron salt includes but is not limited to iron nitrate, and the concentration of the iron salt in the hydrothermal solution is 0.2-0.5 mmol / L; the alkaline substance includes but is not limited to any one or more of urea, hexamethylenetetraammonium or triethanolamine, and the concentration of the alkaline substance in the hydrothermal solution is 1-20 mmol / L.

[0085] The hydrothermal temperature used in the hydrothermal method can be 80-150° C., preferably 90-120° C., and the hydrothermal time can be 4-48 hours, preferably 8-12 hours. The method for co-depositing nickel iron barium by hydrothermal method includes placing a conductive substrate in a hydrothermal solution and heating it, depositing barium ions in the solution onto the conductive substrate, and dispersing them into the catalyst at the atomic level.

[0086] In one embodiment, the preparation method of the electrolytic hydrogen production anode specifically includes: immersing a conductive substrate in a hydrothermal solution, mixing and stirring to form the nickel-iron-barium hydrotalcite; the hydrothermal solution is prepared by dissolving alkaline earth metal salts, nickel salts and iron salts, as well as additional alkaline substances in water, and the amount of water used is 35 to 50 mL; the rotation speed of the mixing and stirring is 800 to 1200 rpm.

[0087] In summary, it can be seen that the above preferred hydrothermal method is different from the existing preparation process of hydrothermal nickel-iron hydrotalcite anode. For example, its barium salt concentration, nickel salt and iron salt concentration ratio are different from the existing preparation process of hydrothermal nickel-iron hydrotalcite anode. This is a change made to form the above nanolayer structure.

[0088] In one embodiment, a method for activating an electrolytic hydrogen production anode includes activating the electrolytic hydrogen production anode in an alkaline solution containing sulfate.

[0089] Specifically, the activation method of the electrolytic hydrogen production anode includes: activating the electrolytic hydrogen production anode by cyclic voltammetry in a sulfate solution. The solution used in the cyclic voltammetry includes an alkaline substance and a sulfate, the alkaline substance includes sodium hydroxide or potassium hydroxide, and the sulfate may include sodium sulfate, but is not limited thereto. The concentration of the alkaline substance in the solution is 0.1 to 1 mol / L, and the concentration of the sulfate is 0.01 to 0.1 mol / L.

[0090] The test system used in the cyclic voltammetry method can be a three-electrode system, the counter electrode used is a carbon rod, and the reference electrode used is a silver / silver chloride electrode; the ambient temperature used in the cyclic voltammetry method is 20-25°C, the number of scanning circles used is 10-30 circles, the scanning voltage range used is 0V-1V, and the scanning voltage rate used is 5mV / s-50mV / s.

[0091] From the above, it can be seen that the above preferred activation method is a unique activation method of the present application, and its scanning voltage rate, scanning voltage range and electrode system are different from the existing anode activation process. This is a change made to fix the above sulfate activation layer.

[0092] Some embodiments of the present application also provide the use of the electrolytic hydrogen production catalyst, the activated electrolytic hydrogen production catalyst or the electrolytic hydrogen production anode in electrolytic hydrogen production.

[0093] In one embodiment, the application includes: placing the electrolytic hydrogen production anode and cathode into an aqueous solution containing chloride ions, and applying a working voltage between the anode and cathode.

[0094] Some embodiments of the present application also provide an application of the electrolytic hydrogen production catalyst in electrolytic hydrogen production, the application comprising: placing an electrolytic hydrogen production anode and a cathode in an aqueous solution containing chloride ions and sulfate ions, and applying a working voltage between the anode and the cathode, thereby achieving electrolytic hydrogen production; the anode comprises the electrolytic hydrogen production catalyst.

[0095] Some embodiments of the present application also provide a method for producing hydrogen by electrolysis, comprising: placing the anode and cathode of the hydrogen production by electrolysis into an aqueous solution containing chloride ions, and applying a working voltage between the anode and the cathode, thereby achieving hydrogen production by electrolysis.

[0096] In one embodiment, the aqueous solution containing chloride ions includes but is not limited to seawater or chlorine-containing industrial wastewater, etc. Preferably, the aqueous solution containing chloride ions is alkaline.

[0097] Taking the aqueous solution containing chloride ions as seawater as an example, the electrolytic hydrogen production method is used at a temperature of 25°C, a voltage of 2V, a distance between the anode and the cathode of 1cm, and an anode surface area of ​​1cm. 2Under the conditions, the hydrogen evolution efficiency can reach more than 0.27L / hour.

[0098] Some embodiments of the present application also provide an electrolytic hydrogen production system, comprising an anode and a cathode, wherein the electrolytic hydrogen production system is used to produce hydrogen by electrolyzing an aqueous solution containing chloride ions, and the anode comprises the electrolytic hydrogen production anode.

[0099] In one embodiment, the aqueous solution containing chloride ions includes but is not limited to seawater or chlorine-containing industrial wastewater. In specific implementation, due to cost considerations, the optimal choice of the aqueous solution containing chloride ions is seawater.

[0100] In some cases, the electrolytic hydrogen production system may further include a power source, etc. The cathode may be made of Pt, Ni, RaneyNi, NiMo alloy, etc.

[0101] This application provides a new idea for improving the stability of the anode during seawater electrolysis to produce hydrogen.

[0102] The technical solution of the present application is further described in detail below through several embodiments and in combination with the accompanying drawings. However, the selected embodiments are only used to illustrate the present application, and do not limit the scope of the present application. Also, unless otherwise specified, the raw materials, detection reagents and detection equipment used in the following embodiments can all be purchased from the market, and the detection methods used are also commonly used in the art. For example, the nickel foam used below is commercial nickel foam, and it is cleaned before use. The specific cleaning method includes: cutting the commercial nickel foam into 1cm×4cm strips, rinsing in 2mol·L -1 The samples were ultrasonically treated in a hydrochloric acid solution for 3 min, and then ultrasonically cleaned in deionized water and anhydrous ethanol three times respectively, and then dried naturally in air.

[0103] Example 1

[0104] (1) Nickel nitrate hexahydrate, barium nitrate, iron nitrate nonahydrate, and hexamethylenetetraammonium were weighed and dissolved in 35 mL of deionized water at a molar ratio of 5:0.5:5:10 to prepare a solvothermal reaction solution containing nickel, iron, and barium, and the solution was transferred into a 50 mL polytetrafluoroethylene reaction tank.

[0105] (2) Using nickel foam as a conductive substrate, immersing the cleaned conductive substrate into the reaction solution, sealing it in a stainless steel high-pressure reactor for 48 hours of solvent thermal reaction at 80°C, cooling it out and washing it with ultrapure water and ethanol, placing it in an oven, and drying it in air at 60°C for 12 hours. A highly stable NiFeBa / NF oxygen evolution anode (hereinafter also referred to as NiFeBa / NF anode or electrolytic hydrogen production anode) is obtained.

[0106] (3) Weigh 20 g of sodium hydroxide and 146.1 g of chloride and dissolve them in 1 L of deionized water to prepare a low-alkali, high-salt concentration simulated seawater solution containing 0.5 M NaOH and 2.5 M NaCl.

[0107] (4) The NiFeBa / NF anode prepared in step (2) was used as the working electrode, the platinum sheet was used as the counter electrode, and the low-alkali high-salt concentration simulated seawater in step (3) was used as the electrolyte. 2 The stability of NiFeBa / NF was tested at a current density of .

[0108] As a control, the barium nitrate in step (1) was omitted, and the remaining operations and process conditions were the same as steps (1) to (2), and finally a NiFe-LDH / NF anode was prepared. Then, its stability was tested in the same manner as step (4).

[0109] The test results show that the stability of the NiFeBa / NF anode prepared in this example is maintained for about 2 hours in the harsh simulated seawater electrolysis, while the NiFe-LDH / NF anode can only operate for 30 minutes in the same solution environment, indicating that the NiFeBa / NF anode prepared in this example plays a role in protecting the conductive substrate.

[0110] Example 1-1

[0111] The method for preparing a NiFeBa / NF anode provided in this embodiment is basically the same as that in Embodiment 1, except that the reaction temperature of the solvent thermal reaction in step (2) is 90° C. and the reaction time is 12 h.

[0112] The stability of the NiFeBa / NF anode of this embodiment was tested by the same method as in Example 1. The test results showed that the stability of the NiFeBa / NF anode prepared in this embodiment was maintained for about 3 hours in the harsh simulated seawater electrolysis.

[0113] Example 2

[0114] (1) Nickel nitrate hexahydrate, barium nitrate, iron nitrate nonahydrate, and urea were weighed and dissolved in 35 mL of deionized water at a molar ratio of 3:0.6:1:6 to prepare a solvothermal reaction solution containing nickel, iron, and barium, and the solution was transferred into a 50 mL polytetrafluoroethylene reaction tank.

[0115] (2) Using nickel foam as a conductive substrate, the cleaned conductive substrate was immersed in a reaction solution, sealed in a stainless steel high-pressure reactor, and subjected to a solvent thermal reaction at 150°C for 4 hours. After cooling and taking out, it was cleaned with ultrapure water and ethanol, placed in an oven, and dried in air at 60°C for 12 hours to obtain a NiFeBa / NF anode. The X-ray diffraction spectrum of the NiFeBa / NF anode is shown in FIG. Figure 1As shown, the surface morphology is Figure 2 As shown in the TEM image Figure 3 , 4 It is clear that: on the one hand, NiFeBa tightly covers the surface of the conductive substrate, and on the other hand, barium is doped in the nickel-iron hydrotalcite in an atomically dispersed form to form a new anode nickel-iron-barium hydrotalcite. The XPS picture is as follows Figure 6 shown.

[0116] (3) Weigh 40 g of sodium hydroxide and 146.1 g of sodium chloride solid and dissolve them in 1 L of deionized water to prepare a simulated seawater solution containing 1 M NaOH and 2.5 M NaCl.

[0117] (4) The NiFeBa / NF anode prepared in step (2) was used as the working electrode, the platinum sheet was used as the counter electrode, and the high concentration simulated seawater prepared in step (3) was used as the electrolyte. 2 The stability of NiFeBa / NF anode was tested at a current density of Figure 5 shown.

[0118] As a control, the barium nitrate in step (1) was omitted, and the remaining operations and process conditions were the same as steps (1) to (2), and finally a NiFe-LDH / NF anode was prepared. Then, its stability was tested in the same manner as step (4).

[0119] The electrode prepared in this example has a stable working time of up to 120 hours in simulated seawater electrolysis, and its stability is about four times that of NiFe-LDH / NF, which indicates that the NiFeBa / NF anode prepared in this example plays a role in protecting the substrate.

[0120] Example 2-1

[0121] The method for preparing a NiFeBa / NF anode provided in this embodiment is basically the same as that in Embodiment 2, except that the reaction temperature of the solvent thermal reaction in step (2) is 120° C. and the reaction time is 4 h.

[0122] The stability of the NiFeBa / NF anode of this embodiment was tested by the same method as in Example 2. The test results showed that the stability of the NiFeBa / NF anode prepared in this embodiment was maintained for about 140 hours in simulated seawater electrolysis.

[0123] Example 3

[0124] (1) Nickel nitrate hexahydrate, barium nitrate, iron nitrate nonahydrate, and urea were weighed and dissolved in 35 mL of deionized water at a molar ratio of 3:1:3:10 to prepare a solvothermal reaction solution containing nickel, iron, and barium, and the solution was transferred into a 50 mL polytetrafluoroethylene reaction tank.

[0125] (2) Using nickel foam as a conductive substrate, the cleaned conductive substrate was immersed in a reaction solution, sealed in a stainless steel high-pressure reactor, and subjected to solvent thermal reaction at 120°C for 24 hours. After cooling and taking out, the substrate was cleaned with ultrapure water and ethanol, placed in an oven, and dried in air at 60°C for 12 hours to obtain a NiFeBa / NF anode.

[0126] (3) Weigh 20 g of sodium hydroxide, 146.1 g of sodium chloride, and 35.51 g of anhydrous sodium sulfate solid and dissolve them in 1 L of deionized water to prepare a high-concentration simulated seawater solution containing 0.5 M NaOH, 2.5 M NaCl, and 0.25 M Na2SO4.

[0127] (4) The NiFeBa / NF anode prepared in step (2) was used as the working electrode, the platinum sheet was used as the counter electrode, and the low-alkali high-salt concentration simulated seawater in step (3) was used as the electrolyte. 2 The stability of NiFeBa / NF anode was tested at a current density of .

[0128] As a control, the barium nitrate in step (1) was omitted, and the remaining operations and process conditions were the same as steps (1) to (2), and finally a NiFe-LDH / NF anode was prepared. Then, its stability was tested in the same manner as step (4).

[0129] The electrode prepared in this example has a stable working time of up to 18 hours in seawater electrolysis, and its stability is about 8 times that of NiFe-LDH / NF, indicating that the NiFeBa / NF anode prepared in this example plays a role in protecting the substrate.

[0130] Example 3-1

[0131] The method for preparing a NiFeBa / NF anode provided in this embodiment is basically the same as that in Embodiment 2, except that the reaction temperature of the solvent thermal reaction in step (2) is 120° C. and the reaction time is 4 h.

[0132] The stability of the NiFeBa / NF anode of this embodiment was tested by the same method as in Example 3. The test results showed that the stability of the NiFeBa / NF anode prepared in this embodiment was maintained for about 25 hours in simulated seawater electrolysis.

[0133] Example 4

[0134] (1) Nickel nitrate hexahydrate, barium nitrate, iron nitrate nonahydrate, and urea were weighed and dissolved in 35 mL of deionized water at a molar ratio of 5:0.5:5:10 to prepare a solvothermal reaction solution containing nickel, iron, and barium, and the solution was transferred into a 50 mL polytetrafluoroethylene reaction tank.

[0135] (2) Using nickel foam as a conductive substrate, the cleaned conductive substrate was immersed in a reaction solution, sealed in a stainless steel high-pressure reactor for solvent thermal reaction at 120°C for 24 hours, cooled and taken out, cleaned with ultrapure water and ethanol, placed in an oven, and dried in air at 60°C for 12 hours to obtain a highly stable NiFeBa / NF anode.

[0136] (3) Weigh 20 g of sodium hydroxide, 146.1 g of sodium chloride, and 35.51 g of anhydrous sodium sulfate solid and dissolve them in 1 L of deionized water to prepare a high-concentration simulated seawater solution containing 0.5 M NaOH, 2.5 M NaCl, and 0.25 M Na2SO4.

[0137] (4) The NiFeBa / NF anode prepared in step (2) was used as the working electrode, the platinum sheet was used as the counter electrode, and the low-alkali high-salt concentration simulated seawater in step (3) was used as the electrolyte. 2 The stability of NiFeBa / NF anode was tested at a current density of Figure 7 shown.

[0138] As a control, the barium nitrate in step (1) was omitted, and the remaining operations and process conditions were the same as steps (1) to (2), and finally a NiFe-LDH / NF anode was prepared. Then, its stability was tested in the same manner as step (4).

[0139] The NiFeBa / NF anode prepared in this example has a stable working time of up to 20 hours in seawater electrolysis, and its stability is about seven times that of NiFe-LDH / NF, indicating that the NiFeBa / NF anode prepared in this example plays a role in protecting the substrate.

[0140] Based on the above examples, it can be seen that within a suitable barium nitrate concentration range, the stability of the prepared NiFeBa / NF anode is greatly improved compared to NiFe-LDH / NF.

[0141] Example 5

[0142] (1) Nickel nitrate hexahydrate, barium nitrate, iron nitrate nonahydrate, and urea were weighed and dissolved in 35 mL of deionized water at a molar ratio of 4:1:4:8 to prepare a solvothermal reaction solution containing nickel, iron, and barium, and the solution was transferred into a 50 mL polytetrafluoroethylene reaction tank.

[0143] (2) Use nickel foam as the conductive substrate, immerse the cleaned conductive substrate in the reaction solution, seal it in a stainless steel autoclave and perform a solvent thermal reaction at 150°C for 4 hours, cool it down and take it out, clean it with ultrapure water and ethanol, place it in an oven, and dry it in air at 60°C for 12 hours. A highly stable NiFeBa / NF anode is obtained, and its scanning image is shown in the figure below. Figure 8 As shown, it can be seen that NiFeBa / NF tightly covers the surface of the conductive substrate.

[0144] (3) Weigh 40 g of sodium hydroxide, 146.1 g of sodium chloride, and 35.51 g of anhydrous sodium sulfate solid and dissolve them in 1 L of deionized water to prepare a high-concentration simulated seawater solution containing 1 M NaOH, 2.5 M NaCl, and 0.25 M Na2SO4.

[0145] (4) The NiFeBa / NF prepared in step (2) was used as the working electrode, the platinum sheet was used as the counter electrode, and the high concentration simulated seawater prepared in step (3) was used as the electrolyte. 2 The stability of NiFeBa / NF was tested at a current density of Fig. 9 shown.

[0146] As a control, the barium nitrate in step (1) was omitted, and the remaining operations and process conditions were the same as steps (1) to (2), and finally a NiFe-LDH / NF anode was prepared. Then, its stability was tested in the same manner as step (4).

[0147] The NiFeBa / NF anode prepared in this example has a stable working time of more than 600 hours in seawater electrolysis, while the NiFe-LDH / NF anode can only operate for 60 hours, indicating that the NiFeBa / NF anode prepared in this example plays a role in protecting the substrate.

[0148] Example 5-1

[0149] The method for preparing a NiFeBa / NF anode provided in this embodiment is basically the same as that in Embodiment 2, except that the reaction temperature of the solvent thermal reaction in step (2) is 100° C. and the reaction time is 4 h.

[0150] The stability of the NiFeBa / NF anode of this embodiment was tested by the same method as in Example 5. The test results showed that the stability of the NiFeBa / NF anode prepared in this embodiment was maintained for about 630 hours in simulated seawater electrolysis.

[0151] Example 5-2

[0152] The method for preparing a NiFeCa / NF anode provided in this embodiment is basically the same as that in Embodiment 5, except that calcium nitrate is used to replace the barium nitrate used in step (1).

[0153] The stability of the NiFeCa / NF anode of this embodiment was tested by the same method as in Example 5. The test results showed that the stability of the NiFeCa / NF anode prepared in this embodiment was maintained for about 530 hours in simulated seawater electrolysis.

[0154] Example 5-3

[0155] The method for preparing a NiFeSr / NF anode provided in this embodiment is basically the same as that in Embodiment 5, except that strontium nitrate is used to replace the barium nitrate used in step (1).

[0156] The stability of the NiFeSr / NF anode of this embodiment was tested by the same method as in Example 5. The test results showed that the stability of the NiFeSr / NF anode prepared in this embodiment was maintained for about 560 hours in simulated seawater electrolysis.

[0157] Example 6

[0158] (1) Nickel nitrate hexahydrate, barium nitrate, iron nitrate nonahydrate, and urea were weighed and dissolved in 35 mL of deionized water in a molar ratio of 4:0.4:4:6 to prepare a solvothermal reaction solution containing nickel, iron, and barium, and the solution was transferred into a 50 mL polytetrafluoroethylene reaction tank.

[0159] (2) Using nickel foam as a conductive substrate, the cleaned conductive substrate was immersed in a reaction solution, sealed in a stainless steel high-pressure reactor for solvent thermal reaction at 80°C for 48 hours, cooled and taken out, cleaned with ultrapure water and ethanol, placed in an oven, and dried in air at 60°C for 12 hours to obtain a highly stable NiFeBa / NF anode.

[0160] (3) Weigh 40 g of sodium hydroxide and 29.22 g of sodium chloride solid and dissolve them in 1 L of deionized water to prepare a simulated seawater solution containing 1 M NaOH and 0.5 M NaCl.

[0161] (4) The NiFeBa / NF anode prepared in step (2) was used as the working electrode, the platinum sheet was used as the counter electrode, and the simulated seawater prepared in step (3) was used as the electrolyte. 2 The stability of NiFeBa / NF was tested at a current density of Fig.10 shown.

[0162] As a control, the barium nitrate in step (1) was omitted, and the remaining operations and process conditions were the same as steps (1) to (2), and finally a NiFe-LDH / NF anode was prepared. Then, its stability was tested in the same manner as step (4).

[0163] The NiFeBa / NF anode prepared in this example has a stable working time of up to 500 hours in seawater electrolysis, and its stability is about twice that of NiFe-LDH / NF, indicating that the NiFeBa / NF anode prepared in this example has a certain degree of improvement in protecting the substrate without adding sulfate.

[0164] Example 6-1

[0165] The method for preparing a NiFeBa / NF anode provided in this embodiment is basically the same as that in Example 2, except that the reaction temperature of the solvent thermal reaction in step (2) is 90° C. and the reaction time is 12 h.

[0166] The stability of the NiFeBa / NF anode of this embodiment was tested by the same method as in Example 6. The test results showed that the stability of the NiFeBa / NF anode prepared in this embodiment was maintained at about 550 hours in simulated seawater electrolysis.

[0167] Example 7

[0168] (1) Nickel nitrate hexahydrate, barium nitrate, iron nitrate nonahydrate, and urea were weighed and dissolved in 35 mL of deionized water at a molar ratio of 5:1:1.5:10 to prepare a solvothermal reaction solution containing nickel, iron, and barium, and the solution was transferred into a 50 mL polytetrafluoroethylene reaction tank.

[0169] (2) Using nickel foam as a conductive substrate, the cleaned conductive substrate was immersed in a reaction solution, sealed in a stainless steel high-pressure reactor for solvent thermal reaction at 120°C for 24 hours, cooled and taken out, cleaned with ultrapure water and ethanol, placed in an oven, and dried in air at 60°C for 12 hours to obtain a highly stable NiFeBa / NF anode.

[0170] (3) Weigh 40 g of sodium hydroxide, 29.22 g of sodium chloride, and 7.1 g of sodium sulfate solid and dissolve them in 1 L of deionized water to prepare a simulated seawater solution containing 1 M NaOH, 0.5 M NaCl, and 0.05 M Na2SO4.

[0171] (4) The NiFeBa / NF anode prepared in step (2) was used as the working electrode, the platinum sheet was used as the counter electrode, and the simulated seawater prepared in step (3) was used as the electrolyte. 2 The stability of NiFeBa / NF was tested at a current density of Fig.11 shown.

[0172] As a control, the barium nitrate in step (1) was omitted, and the remaining operations and process conditions were the same as steps (1) to (2), and finally a NiFe-LDH / NF anode was prepared. Then, its stability was tested in the same manner as step (4).

[0173] The NiFeBa / NF anode prepared in this example has been running stably for 4000 hours in seawater electrolysis. Its stability is currently about 3 times that of NiFe-LDH / NF, indicating that the NiFeBa / NF anode prepared in this example has excellent stability.

[0174] Example 8

[0175] (1) Nickel nitrate hexahydrate, barium nitrate, iron nitrate nonahydrate, and urea were weighed and dissolved in 35 mL of deionized water in a molar ratio of 2:0.6:2:6 to prepare a solvothermal reaction solution containing nickel, iron, and barium, and the solution was transferred into a 50 mL polytetrafluoroethylene reaction tank.

[0176] (2) Using nickel foam as a conductive substrate, the cleaned conductive substrate was immersed in the reaction solution, sealed in a stainless steel high-pressure reactor for solvent thermal reaction at 120°C for 24 hours, cooled and taken out, cleaned with ultrapure water and ethanol, placed in an oven, and dried in air at 60°C for 12 hours. A highly stable NiFeBa / NF anode was obtained.

[0177] (3) Weigh 40 g of sodium hydroxide and 142.04 g of anhydrous sodium sulfate solid and dissolve them in 1 L of deionized water to prepare an electrolyte solution containing 1 M NaOH and 1 M Na2SO4 for later use. The NiFeBa / NF prepared in step (2) is used as the working electrode and the platinum sheet is used as the counter electrode. The electrolyte solution containing 1 M NaOH and 1 M Na2SO4 is used at 400 mA / cm 2 The NiFeBa / NF anode was activated at a current density of for 1 h to obtain an activated NiFeBa / NF anode.

[0178] (4) Weigh 40 g of sodium hydroxide and 146.1 g of sodium chloride solid and dissolve them in 1 L of deionized water to prepare a high-concentration simulated seawater solution containing 1 M NaOH and 2.5 M NaCl.

[0179] (5) The activated NiFeBa / NF anode prepared in step (3) was used as the working electrode, the platinum sheet was used as the counter electrode, and the high concentration simulated seawater prepared in step (4) was used as the electrolyte. 2 The stability of NiFeBa / NF anode was tested at a current density of Fig.12 shown.

[0180] The activated NiFeBa / NF anode prepared in this example has a stable working time of up to 310 hours in seawater electrolysis, while the NiFe-LDH / NF anode can only operate for 30 hours, indicating that the activated NiFeBa / NF anode prepared in this example plays a role in protecting the substrate.

[0181] As a control, if the above step (3) is omitted and the NiFeBa / NF anode of step (2) is directly tested in step (5), the results show that without activation, the activated NiFeBa / NF anode prepared in this embodiment has a stable working time of 30 hours in a high concentration simulated seawater solution of 1M NaOH and 2.5M NaCl.

[0182] Comparative Example 1

[0183] (1) Nickel nitrate hexahydrate, iron nitrate nonahydrate, and urea were weighed and dissolved in 35 mL of deionized water at a molar ratio of 5:5:10 to prepare a nickel-iron solvent thermal reaction solution, which was then transferred into a 50 mL polytetrafluoroethylene reaction tank.

[0184] (2) Using nickel foam as a conductive substrate, the cleaned conductive substrate was immersed in a reaction solution, sealed in a stainless steel high-pressure reactor, and subjected to solvent thermal reaction at 120°C for 24 hours. After cooling and taking out, the substrate was cleaned with ultrapure water and ethanol, placed in an oven, and dried in air at 60°C for 12 hours to obtain a NiFe-LDH / NF anode.

[0185] (3) Weigh 40 g of sodium hydroxide and 146.1 g of sodium chloride solid and dissolve them in 1 L of deionized water to prepare a simulated seawater solution containing 1 M NaOH and 2.5 M NaCl.

[0186] (4) The NiFe-LDH / NF prepared in step (2) was used as the working electrode, the platinum sheet was used as the counter electrode, and the simulated seawater prepared in step (3) was used as the electrolyte. 2 The stability of NiFe-LDH / NF was tested at a current density of Fig.13 The stability of the NiFe-LDH / NF anode prepared in this comparative example is about 30 hours, and its activity is basically the same as that of the NiFeBa / NF anode used as a control, but its stability is poor. The NiFeBa / NF anode used as a control is prepared in a method basically the same as that of Example 4, except that the temperature of the hydrothermal reaction is 120°C.

[0187] Comparative Example 2

[0188] (1) Weigh nickel nitrate hexahydrate, iron nitrate nonahydrate, and urea in a molar ratio of 5:5:10 and dissolve them in 35 mL of deionized water to prepare a nickel-iron solvent thermal reaction solution, which is then transferred to a 50 mL polytetrafluoroethylene reaction tank.

[0189] (2) Using nickel foam as a conductive substrate, immersing the cleaned conductive substrate into the reaction solution, sealing it in a stainless steel autoclave for solvent thermal reaction at 150°C for 4 hours, cooling it out, cleaning it with ultrapure water and ethanol, placing it in an oven, and drying it in air at 60°C for 12 hours to obtain a NiFe-LDH / NF anode.

[0190] (3) Weigh 40 g of sodium hydroxide and 29.22 g of sodium chloride solid and dissolve them in 1 L of deionized water to prepare a simulated seawater solution containing 1 M NaOH and 0.5 M NaCl.

[0191] (4) The NiFe-LDH / NF anode prepared in step (5) was used as the working electrode, the platinum sheet was used as the counter electrode, and the simulated seawater prepared in step (3) was used as the electrolyte. 2 The stability of NiFe-LDH / NF was tested at a current density of Fig.14 The NiFe-LDH / NF anode prepared in this comparative example has poor stability, which is about 230 hours, far lower than the NiFeBa / NF anode in Example 4 above.

[0192] Comparative Example 3

[0193] (1) Weigh nickel nitrate hexahydrate, iron nitrate nonahydrate, and urea in a molar ratio of 5:5:10 and dissolve them in 35 mL of deionized water to prepare a nickel-iron solvent thermal reaction solution, which is then transferred to a 50 mL polytetrafluoroethylene reaction tank.

[0194] (2) Using nickel foam as a conductive substrate, the cleaned conductive substrate was immersed in a reaction solution, sealed in a stainless steel high-pressure reactor for solvent thermal reaction at 90°C for 48 hours, cooled and taken out, cleaned with ultrapure water and ethanol, placed in an oven, and dried in air at 60°C for 12 hours to obtain a NiFeBa / NF anode.

[0195] (3) Weigh 40 g of sodium hydroxide, 29.22 g of sodium chloride, and 7.1 g of sodium sulfate solid and dissolve them in 1 L of deionized water to prepare a simulated seawater solution containing 1 M NaOH, 0.5 M NaCl, and 0.05 M Na2SO4.

[0196] (4) The NiFe-LDH / NF anode prepared in step (2) was used as the working electrode, the platinum sheet was used as the counter electrode, and the simulated seawater prepared in step (3) was used as the electrolyte. 2 The stability of NiFe-LDH / NF anode was tested at a current density of Fig.15 The NiFe-LDH / NF anode prepared in this comparative example has poor stability, which is about 800 hours, far lower than the NiFeBa / NF anode in the above Example 4.

[0197] At a temperature of 25°C, a voltage of 2V, a distance of 1cm between the anode and cathode, and an anode surface area of ​​1cm 2 Under the conditions, the simulated seawater in Example 7 was electrolyzed by the anodes of Examples 1 to 8 to produce hydrogen, and the hydrogen evolution efficiencies were 0.272, 0.268, 0.271, 0.265, 0.267, 0.270, 0.273, and 0.266 L / hour, respectively. Under the same conditions, the simulated seawater in Example 1 was electrolyzed by the anodes of Comparative Examples 1 to Comparative Examples 3 to produce hydrogen, and the hydrogen evolution efficiencies were 0.257, 0.251, and 0.254 L / hour, respectively.

[0198] In addition, the inventors also prepared NiFeBa / NF anodes using commercial nickel mesh, commercial foam iron, and commercial foam nickel-iron as conductive substrates instead of the nickel foam in Examples 1 to 8, and tested the stability and electrolytic hydrogen production efficiency of these NiFeBa / NF anodes using the same test methods as Examples 1 to 8. The test results showed that these NiFeBa / NF anodes all exhibited excellent stability and high electrolytic hydrogen production efficiency.

[0199] Example 9 The preparation method of a NiFeCa / NF anode is basically the same as that of Example 3, except that barium nitrate is replaced by calcium nitrate.

[0200] Example 9-1 The preparation method of a NiFeCa / NF anode is basically the same as that of Example 3-1, except that barium nitrate is replaced by calcium nitrate.

[0201] Example 10 A method for preparing a NiFeSr / NF anode is basically the same as that of Example 3, except that barium nitrate is replaced by strontium nitrate.

[0202] Example 10-1 A method for preparing a NiFeSr / NF anode is basically the same as that of Example 3-1, except that barium nitrate is replaced by strontium nitrate.

[0203] The anode performances of Examples 9, 9-1, 10, and 10-1 were tested with reference to the methods of Example 3 and Example 3-1. The results are shown in Table 1 below.

[0204] Table 1 Anode performance test results of Examples 9, 9-1, 10, and 10-1

[0205] Example Test environment stability 9 <![CDATA[0.5M NaOH+2.5M NaCl+0.25M Na2SO4]]> 13h 9-1 <![CDATA[0.5M NaOH+2.5M NaCl+0.25M Na2SO4]]> 20h 10 <![CDATA[0.5M NaOH+2.5M NaCl+0.25M Na2SO4]]> 16h 10-1 <![CDATA[0.5M NaOH+2.5M NaCl+0.25M Na2SO4]]> 22h

[0206] Based on the above embodiments, it can be seen that the electrode hydrogen production catalyst provided in the present application enables the surface of the electrode hydrogen production anode to have a higher resistance to chloride ions, which can significantly delay the corrosion of chloride ions on the conductive substrate and the catalyst in seawater electrolysis, thereby making the anode have excellent stability in the process of hydrogen production by electrolysis of chlorine-containing aqueous solution, especially in the hydrogen production reaction by electrolysis in seawater.

[0207] The above-mentioned embodiments of the present application prepare NiFeBa / NF, NiFeCa / NF, NiFeSr / NF oxygen evolution catalysts densely coated on a conductive substrate by a simple hydrothermal method, and use non-precious metals as the catalyst metal source, which has the advantage of low cost and significantly extends the service life of the electrolytic hydrogen production anode.

[0208] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present application, and their purpose is to enable people familiar with the technology to understand the content of the present application and implement it accordingly, and they cannot be used to limit the protection scope of the present application. Any equivalent changes or modifications made according to the spirit of the present application should be included in the protection scope of the present application.

Claims

1. A catalyst for hydrogen production by electrolysis, characterized in that: The chemical formula of the catalyst is [M 1-x N x M'(OH)2] x+ [(A n- ) x / n ·mH2O] x- , M and N are any two ions of iron, cobalt and nickel, and M and N are in the chemical valence states of +2 and +3 respectively, and M' is selected from Ca 2+ , Sr 2+ Or Ba 2+ and is dispersed at the atomic level in the catalyst, A n- Selected from CO3 2- or SO4 2- , x=0.17~0.33, m is an integer greater than or equal to 0, and n=1~3.

2. The electrolytic hydrogen production catalyst according to claim 1, characterized in that: The atomic percentage content of M' in the catalyst is 0.4% to 0.5%.

3. The electrolytic hydrogen production catalyst according to claim 1, characterized in that: M' is Ba 2+ .

4. The electrolytic hydrogen production catalyst according to claim 1, characterized in that: M and N are Ni 2+ , Fe 3+ , M' is Ba 2+ , A n- For CO3 2- .

5. The electrolytic hydrogen production catalyst according to any one of claims 1 to 4, characterized in that: The catalyst has a nano hexagonal sheet structure.

6. The electrolytic hydrogen production catalyst according to claim 5, characterized in that: The nano hexagonal sheet structure has at least one of the following characteristics: a) a thickness of 100 to 200 nm; b) an area of ​​0.01 to 0.05 μm 2 .

7. A method for preparing a catalyst for hydrogen production by electrolysis, characterized in that: include: The mixed reaction liquid containing M, N and M' is subjected to a hydrothermal reaction to obtain an electrolytic hydrogen production catalyst, wherein the chemical formula of the catalyst is [M 1-x N x M'(OH)2] x+ [(A n- ) x / n ·mH2O] x- , where M and N are any two ions of iron, cobalt, and nickel, and M and N are in the chemical valence states of +2 and +3 respectively, and M' is selected from Ca 2+ , Sr 2+ Or Ba 2+ and is dispersed at the atomic level in the catalyst, A n- Selected from CO3 2- or SO4 2- , x=0.17~0.33, m is an integer greater than or equal to 0, and n=1~3.

8. The preparation method according to claim 7, characterized in that: Specifically include: The catalyst is prepared by subjecting a mixed reaction liquid containing a first transition metal compound, a second transition metal compound and an alkaline earth metal compound in a molar ratio of 2-5:2-5:0.4-1 to a hydrothermal reaction at 90-120° C., wherein the first transition metal compound, the second transition metal compound and the alkaline earth metal compound contain M, N and M′ respectively, and the pH value of the mixed reaction liquid is 8-10.

9. The preparation method according to claim 8, characterized in that: Specifically include: The first transition metal compound, the second transition metal compound, the alkaline earth metal compound and water are mixed to form a metal salt solution, and an alkaline substance is added to adjust the pH value of the metal salt solution to 8-10, thereby obtaining the mixed reaction solution; The mixed reaction liquid is reacted at 90-120° C. for 8-12 hours to obtain the catalyst.

10. The preparation method according to any one of claims 8 to 9, characterized in that: The atomic percentage content of M' in the catalyst is 0.4% to 0.5%.

11. The preparation method according to claim 10, characterized in that: M' is Ba 2+ .

12. The preparation method according to claim 11, characterized in that: M and N are Ni 2+ , Fe 3+ , M' is Ba 2+ , A n- For CO3 2- .

13. The preparation method according to any one of claims 11 to 12, characterized in that: The first transition metal compound includes a soluble nickel salt, the second transition metal compound includes a soluble iron salt, and the alkaline earth metal compound includes a soluble barium salt.

14. The preparation method according to claim 13, characterized in that: The nickel salt includes nickel nitrate, the iron salt includes iron nitrate, and the soluble barium salt includes barium nitrate.

15. The preparation method according to any one of claims 8 to 9, characterized in that: The concentrations of the first transition metal compound, the second transition metal compound and the alkaline earth metal compound contained in the mixed reaction liquid are 0.1-1 mmol / L, 0.2-0.5 mmol / L and 0.1-1 mmol / L respectively.

16. The preparation method according to claim 9, characterized in that: The alkaline substance includes any one or more combinations of urea, hexamethylenetetraammonium or triethanolamine.

17. The method for activating a catalyst for producing hydrogen by electrolysis according to any one of claims 1 to 6, characterized in that: include: The catalyst is placed in an alkaline solution containing sulfate ions, wherein the pH value of the alkaline solution is 13-14, and an activation treatment is performed by an electrochemical method.

18. The activation method according to claim 17, characterized in that: The electrochemical method includes one or more combinations of cyclic voltammetry, linear sweep voltammetry and constant current charge and discharge method.

19. The activation method according to claim 18, characterized in that: The electrochemical method is cyclic voltammetry, wherein the scanning voltage used is 0V-1V, the scanning voltage speed is 5mV / s-50mV / s, the scanning number is 10-30 circles, and the scanning environment temperature is room temperature.

20. The activation method according to claim 17, characterized in that: The alkaline solution contains sulfate ions at a concentration of 0.01 to 0.1 mol / L.

21. The activation method according to claim 20, characterized in that: The alkaline solution contains sulfate, and the sulfate includes sodium sulfate or potassium sulfate.

22. The activation method according to claim 17, characterized in that: The alkaline solution contains alkaline substances with a concentration of 0.1 to 1 mol / L.

23. The activation method according to claim 22, characterized in that: The alkaline substance includes sodium hydroxide or potassium hydroxide.

24. An activated electrolytic hydrogen production catalyst, characterized in that: The invention comprises the electrolytic hydrogen production catalyst according to any one of claims 1 to 6 and a sulfate activation layer, wherein the sulfate activation layer comprises sulfate ions distributed on the surface of the catalyst, and the sulfate ions are combined with alkaline earth metal ions in the catalyst.

25. The activated hydrogen electrolysis catalyst according to claim 24, characterized in that: The nano-layer structure is distributed on the surface of the catalyst, wherein the nano-layer structure comprises a plurality of nano-particles, the particle size of the nano-particles is greater than 0 but less than 5 nm, and the nano-particles are formed by combining the sulfate ions with the alkaline earth metal ions in the catalyst.

26. An anode for producing hydrogen by electrolysis, characterized in that: The anode comprises the hydrogen production by electrolysis catalyst according to any one of claims 1 to 6 or the activated hydrogen production by electrolysis catalyst according to any one of claims 24 to 25.

27. The anode for producing hydrogen by electrolysis according to claim 26, characterized in that: A plurality of the catalyst nanosheets are vertically arranged on the surface of the anode and densely arranged to form an array structure.

28. The anode for producing hydrogen by electrolysis according to claim 27, characterized in that: The specific surface area of ​​the array structure is 40 to 50 m 2 / g.

29. The anode for producing hydrogen by electrolysis according to any one of claims 26 to 28, characterized in that: The anode further comprises a conductive substrate for supporting the catalyst, wherein the conductive substrate comprises foamed nickel, nickel mesh, foamed iron or foamed nickel-iron.

30. Use of the hydrogen production by electrolysis catalyst according to any one of claims 1 to 6, the activated hydrogen production by electrolysis catalyst according to any one of claims 24 to 25, or the hydrogen production by electrolysis anode according to any one of claims 26 to 29 in hydrogen production by electrolysis.

31. The use according to claim 30, characterized in that The application comprises: placing the electrolytic hydrogen production anode and cathode into an aqueous solution containing chloride ions, and applying a working voltage between the anode and cathode.

32. The use according to claim 31, characterized in that: The aqueous solution containing chloride ions includes seawater or chlorine-containing industrial wastewater.

33. Use of the electrolytic hydrogen production catalyst according to any one of claims 1 to 6 in electrolytic hydrogen production, the application comprising: The electrolytic hydrogen production anode and cathode are placed in an aqueous solution containing chloride ions and sulfate ions, and a working voltage is applied between the anode and cathode to achieve electrolytic hydrogen production; the anode includes the electrolytic hydrogen production catalyst.

34. A method for producing hydrogen by electrolysis, characterized in that: include: The electrolytic hydrogen production anode and cathode according to any one of claims 26 to 29 are placed in an aqueous solution containing chloride ions, and a working voltage is applied between the anode and cathode, thereby realizing electrolytic hydrogen production.

35. The method for producing hydrogen by electrolysis according to claim 34, characterized in that: The aqueous solution containing chloride ions includes seawater or chlorine-containing industrial wastewater.

36. A hydrogen production system by electrolysis, comprising an anode and a cathode, characterized in that: The electrolytic hydrogen production system is used for producing hydrogen by electrolyzing an aqueous solution containing chloride ions, and the anode comprises the electrolytic hydrogen production anode according to any one of claims 26 to 29.

37. The electrolysis hydrogen production system according to claim 36, characterized in that: The aqueous solution containing chloride ions includes seawater or chlorine-containing industrial wastewater.

Citation Information

Patent Citations

  • Ferronickel hydrotalcite-like / ferronickel sulfide heterostructure seawater oxidation electrocatalyst and preparation method thereof

    CN114657591A

  • Nickel-iron hydrotalcite / nickel-iron sulfide heterostructure seawater oxidation electrocatalyst and its preparation method

    CN114657591B

  • Catalyst and anode for electrolytic production of hydrogen, and preparation methods therefor, activation methods therefor and use thereof

    WO2024255512A1